Pengaruh Mekanisme GCG, Anti-Fraud Awareness, Sistem Pengendalian Internal, dan Peran Audit Internal terhadap Pencegahan Fraud - Nurul Lailati Mubarokah; Sovi Ismawati Rahayu (Lembaga Penelitian Universitas YARSI, 2024)
The purpose of this study is to investigate how internal audit, internal control systems, anti-fraud awareness, and good corporate governance mechanisms affect PT. Bank Mandiri Jakarta Cikini Area's ability to prevent fraud. By distributing questionnaires, primary data for the study was obtained. 41 members of an internal auditing team participated in this study as respondents. Non-probability sampling is used in this sampling technique. The findings of the study demonstrate that internal audit, internal control systems, anti-fraud awareness, and good corporate governance practices all significantly impact PT. Bank Mandiri Jakarta Cikini Area's ability to prevent fraud. The research's managerial implications include enhancing internal audit's function, bolstering internal control systems, raising anti-fraud awareness across the organization, and fortifying Good Corporate Governance (GCG) mechanisms as a means of preventing fraud. It is imperative that managers give particular attention to the implementation and upkeep of GCG practices, the creation of thorough anti-fraud training programs, the reinforcement of internal control infrastructure, and the allocation of sufficient resources to the internal audit function.